ECB-BASIR: A primer on the macroeconomic implications of the Covid-19 pandemic - Elena Angelini; Milan Damjanovic; Matthieu Darracq Pariès; Sreécko Zimic (European Central Bank (ECB), 2020)
This paper studies the macroeconomic consequences of the COVID-19 pandemic and makes a first step in adapting the central bank modelling apparatus to the new economic landscape. We augment the ECB-BASE model with the predictive dynamics of the SIR model in order to assess the interplay between epidemiological fundamentals, containment policies and the macroeconomy. Containment policies considerably reduce the share of infected and deceased people, but generate a sharp decline in economic activity. Barring the materialization of amplification risks, the induced recession may remain broadly V-shaped under targeted confinement policies. By comparison, a "laissez-faire" approach to the pandemic emergency can even inflict in some cases higher long-term economic costs. Nevertheless, the depth of the recession and the speed of the recovery (if at all) crucially depend on the magnitude and persistence of the supply-side retrenchment, as well as on the risk of macro-financial feedback loops.
Keywords: E1; E3; I1; 330; Epidemic; modelling; COVID-19; ECB-BASE